Structural and magnetic properties of He+ irradiated Co2MnSi Heusler alloys. (18th April 2016) - Abdallah, I; Ratel-Ramond, N; Magen, C; Pecassou, B; Cours, R; Arnoult, A; Respaud, M; Bobo, J F; BenAssayag, G; Snoeck, E; Biziere, N
Abstract: We have investigated the atomic disorder induced by a 150 keV He + ion irradiation in a 40 nm thick Co2 MnSi Heusler alloy. Disorder parameters on each atomic site are deduced from normal and anomalous x-ray diffraction measurements with Co and Cu K α sources. While the film grows mainly in the L21 phase with inclusion of B2 grains, we observe an increase of both the Mn–Si and Co–Mn exchanges with the ion fluence. HAADF-STEM analysis demonstrates that the increase in Mn–Si disorder corresponds to a growing size of the B2 grains while the Co–Mn exchange is accounted for a D03 disorder type in the L21 matrix. These structural modifications are shown to decrease the average magnetization of the alloy, which is due to D03 disorder and local defects induced by irradiation.